Sustainable Machining of Aerospace Material - Boswell, Brian; Islam, Mohammad Nazrul; Pramanik, Alokesh (IAENG, 2013)
The need for optimum machining parameters has always been of great concern to the aerospace industry, as the economy of the process largely depends on selecting the best machining parameters for the machine. However, the additional challenge of being environmentally friendly in production while still being cost effective is now imperative. Metal cutting conditions do not always allow companies to reduce the carbon footprint easily. This is particularly pertinent when newer aerospace material such as Boron Carbide Particle Reinforced Aluminium Alloy (AMC220bc) is machined. This material falls under the category of a particulate reinforced Metal Matrix Composite (MMC), where the ceramic fibers disrupt the flow of electrons, resulting in a decrease in thermal conductivity causing the tool interface temperature to increase reducing tool life. This paper will determine the optimum sustainable machining parameters for this material.